Sistem Informasi Trayek Angkutan Umum Berbasis Web - Tri Wahyu Widyaningsih (Universitas Multimedia Nusantara, 2018)
One way to reduce congestion in big cities is by reducing the use of private vehicles. That is by improving the service and convenience of public transport such as accessing route information easily. The Web Based Public Transportation Information System is designed using SDLC. The system is expected to be able to assist the public in accessing the route information of public transportation on land. The results of this study is a web-based application interface that includes public transportation routes in the Jakarta, Depok, Tangerang, and Bekasi. Index Terms— Information System, Public Transport Route, SDLC, Web Based, Jadetabek.